Cemitérios municipais de Curitiba: instalações e influência na qualidade das águas subterrâneas - Born, Cristiane Maria (2011)
The burial of the bodies is a common practice for men, reflecting their beliefs and religious values. After death, the body goes through a natural process of decomposition, resulting in the generation of a leachate. However, the cemeteries have not been included in the lists of the traditional sources of environmental contamination, despite of being recognized as such by environmental legislation. This study aims to evaluate the facilities of the general municipal cemeteries in Curitiba and their possible influence on the groundwater quality through the assessment of the situation of the graves, and the vulnerability of the aquifer in these areas. The object of the present study corresponded to four municipal areas of burial: Municipal Cemetery São Francisco de Paula, Municipal Cemetery Água Verde, Municipal Cemetery Boqueirão and Municipal Cemetery Santa Candida. The research involved the selection of the studied areas, survey the sites, the burial vaults structure assessment, the vulnerability of the aquifer and, for the Municipal Cemetery Água Verde, the results of monitoring programs (physical, chemical and microbiological) and the correlation between the parameters for the years 2004, 2007 and 2009, to identify the groundwater contamination from cemetery leachate. The Municipal Cemeteries of Curitiba have 32,132 burial vaults, with a predominance of graves above the ground (21,555 units) and those covered with ornamental stone (15,080 graves). Apparent structural damages were identified in 56.06% of the graves, and the highest incidence of cracks was observed for those built with conventional mortar and unpainted walls. The most frequent damages were cracks in conventional coated graves, graves with partially compromised coating identified by falling plaster, and the lack of paint, suggesting a low rate of space maintenance. The Municipal Cemetery Boqueirão had the highest number of multiple damaged units (3.86 damages per grave) and the Municipal Cemetery São Francisco de Paula had the lowest one (2.07 damages per grave). The Municipal Cemetery Santa Candida corresponds to a high vulnerability area in relation to the aquifer contamination, due to the crystalline basement geological predominance in this region. In relation to the groundwater contamination of the Municipal Cemetery Água Verde, the anomalies found in the results failed to correlate with the graveyard activity, in comparison with the upstream monitoring wells, the results of some parameters that may reflect the influence of natural characteristics of the chemical composition of the Guabirotuba aquifer and the application of different methods of laboratory tests for the same parameter. It is therefore necessary to adopt corrective and preventive measurements to ensure the tightness of graves, applying good engineering practices, as well as monitoring and surveillance for the worst graves, and involving assignees in preventive maintenance. Concerning the monitoring of groundwater quality, a review of technical specifications for contracting specialized laboratories for collection and analysis of samples following standard methods must be implemented to improve the groundwater quality monitoring, in order to ensure the reliability of collected data to be used as effective tools for environmental management.